Factors determining the occurrence of Pleurodeles poireti (Caudata: Salamandridae) on Edough Peninsula, northeastern Algeria. Issue 1 (2nd January 2016) - Ben Hassine, Jihène; Escoriza, Daniel; Bakhouche, Badis
Abstract: Pleurodeles poireti is one of the lesser-known amphibians in the Mediterranean region. This species is strictly endemic to the Edough Peninsula in northeastern Algeria. Here we investigated the factors that determine the presence of P. poireti, by affecting its selection of both aquatic and terrestrial habitats. Aquatic habitats were characterised according to their morphology and the physicochemical parameters of the water. We also examined the topographical and substrate features, plant cover and climatic conditions at the occurrence sites. Our surveys indicated that P. poireti is widely-distributed on the Edough Peninsula. Pleurodeles poireti predominantly breeds in moderate to large water bodies densely covered with emergent vegetation. The water parameters are less influential in its selection of breeding sites, except dissolved oxygen and turbidity, which are usually high at the occupied sites. At the broad spatial scale, P. poireti is positively associated with lowlands in cultivated landscapes. However, the species has a relatively broad niche in the region, and also occurs in cork oak forests. The species tolerates some level of human alteration of the landscape, but some populations close to villages could disappear in response to the combined effects of habitat destruction and the presence of alien fish.